2018
DOI: 10.1111/nmo.13440
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a prebiotic galactooligosaccharide mixture (B‐GOS®) on gastrointestinal symptoms in adults selected from a general population who suffer with bloating, abdominal pain, or flatulence

Abstract: BackgroundPrebiotics exert beneficial effects upon gastrointestinal (GI) environment, but this is not always accompanied with a positive effect on GI symptoms. B‐GOS® is a prebiotic with high selectivity toward bifidobacteria and a variety of other beneficial effects in humans. Here, we investigated its effect on GI symptoms in adults who suffer with bloating, abdominal pain, and flatulence.MethodsIn a double‐blind, placebo‐controlled, crossover study, 83 subjects from the general population who presented with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…The symptoms, measured as a global assessment, were significantly improved, compared with a placebo, in both groups receiving the prebiotic at different doses, but the 3.5 g/day dose resulted in lower symptom scores for flatulence, bloating, and stool consistency [127]. In a double-blind, placebo-controlled, crossover study, in which β-GOS ® treatment (2.75 g/day) was tested in 83 subjects who presented with GI symptoms (abdominal pain, bloating and flatulence), this prebiotic was able to significantly reduce the scores of symptoms, after two weeks of assumption [128].…”
Section: Prebiotics and Gastrointestinal Disordersmentioning
confidence: 99%
“…The symptoms, measured as a global assessment, were significantly improved, compared with a placebo, in both groups receiving the prebiotic at different doses, but the 3.5 g/day dose resulted in lower symptom scores for flatulence, bloating, and stool consistency [127]. In a double-blind, placebo-controlled, crossover study, in which β-GOS ® treatment (2.75 g/day) was tested in 83 subjects who presented with GI symptoms (abdominal pain, bloating and flatulence), this prebiotic was able to significantly reduce the scores of symptoms, after two weeks of assumption [128].…”
Section: Prebiotics and Gastrointestinal Disordersmentioning
confidence: 99%
“…In subjects recruited from the general population with a self‐reported functional bowel disorder (but no diagnosis of IBS), 2 weeks’ consumption of a β‐GOS preparation (2.75 g/day) significantly reduced bloating, flatulence, abdominal pain and urgency vs. placebo, but had no effect on the participants’ number of bowel movements, consistency of stools, quality of life or mood (Vulevic et al . ). While the studies to date on prebiotics and IBS are limited and findings inconsistent, the two trials described above hint that β‐GOS could potentially be beneficial in improving gastrointestinal symptoms in subjects with IBS.…”
Section: Potential Health Effects Of Prebioticsmentioning
confidence: 97%
“…This has been suggested to be due to the absence of fructose within β‐GOS (Vulevic et al . ) [which is present within FOS and inulin; see later section on the low‐Fermentable Oligosaccharides, Disaccharides, Monosaccharides and Polyols (FODMAP) diet] and/or the targeted stimulation of bifidobacteria, which do not produce gas (Falony et al . ), though cross‐feeding can occur between bifidobacteria and species that do produce gas (De Vuyst & Leroy ).…”
Section: Potential Health Effects Of Prebioticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study investigating the effect of β‐GOS on IBS symptoms found improved flatulence, stool consistency, bloating, and restored Bifidobacterium abundance in both low (3.5 g/d) and high (7 g/d) dose groups. Anxiety scores improved only in the high dose group . (See Table ).…”
Section: Prebioticsmentioning
confidence: 97%